MENINGKATKAN KEMAMPUAN PENGUCAPAN KATA MELALUI PENGGUNAAN MEDIA COMPACT DISK PADA ANAK AUTISME KELAS DASAR II di SLB WACANA ASIH ( Single Subject Research ) - Eva - Devi (Jurnal Penelitian Pendidikan Khusus, 2015)
One of the efforts to improve the pronunciation of words through the media compact disc. Research by design Single Subject Research (SSR) with AB design, with a phase called the baseline (initial conditions) and B is called the phase of intervention (treatment) was conducted in order to know the use of compact disk media in an effort to improve the pronunciation of the word autistic child with the initials OL in Basic class 2 in SLB Wacana Asih Padang. Techniques of data analysis is direct visual inspection is the analysis of the data displayed in the chart. The results of the baseline conditions are performed five times the meeting demonstrated the ability of children in the pronunciation of the word is at 0%. While the results after a given intervention is done using a compact disk media for fourteen meetings, word pronunciation skills in children with autism showed varying results which range from 10% to 80. The results of this experiment indicate that the compact disk media can increase the ability of the pronunciation of words in children with autism, it is recommended to teachers in special schools to be able to apply the learning pronunciation of words using the compact disc media. Keywords: Pronunciation Word, Media compact disk